The Implementation of Inclusive Islamic Religion Education in Sibolga State Senior High School - Asari, Hasan; Mukti, Abd; Nasution, Sapirin (Universitas Malikussaleh, 2020)
This study reveals about the factors regarding the implementation of inclusive Islamic religious education in Senior High School in Sibolga. The implementation of inclusive PAI which is the problem in this research is the planning, implementation and evaluation of inclusive PAI in Senior High School in Sibolga. The research method in this research is qualitative research with a phonomenology approach, namely analyzing the factors of inclusive Islamic education at State Senior High School in Sibolga. Based on the findings in this study, it can be concluded that the implementation of inclusive Islamic Education in the Sibolga City Senior High School includes planning that includes the school's vision and mission, school work programs/PAI teachers, curriculum, ex-kul, methods, related activities. Based on the results of the evaluation in this implementation, it can be seen that inclusive PAI has the support of school residents and builds inclusive school residents.